2021
DOI: 10.3390/su13147961
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Maritime Transport for Economic Growth in the European Union: A Panel Data Analysis

Abstract: Maritime transport is one of the main activities of the blue economy, which plays an important role in the EU. In this paper, we aim to assess the impact of maritime transport, related investment, and air pollution on economic growth within 20 countries of the European Union, using eight panel data regression models from 2007 to 2018. Our results confirm that maritime transport, air pollutants (NOx and SO2) from maritime transport, and investment in maritime port infrastructure are indeed positively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Their study proved that carbon emissions are significantly lower due to energy efficiency. Another study by [47] also proved this argument, favoring marine trade as the most energy-efficient and least carbon-emitting trade method. However, Ref.…”
Section: Literature Reviewmentioning
confidence: 79%
“…Their study proved that carbon emissions are significantly lower due to energy efficiency. Another study by [47] also proved this argument, favoring marine trade as the most energy-efficient and least carbon-emitting trade method. However, Ref.…”
Section: Literature Reviewmentioning
confidence: 79%
“…The more urbanized an area is, the more likely it is to have higher levels of economic activity, such as trade, manufacturing, services, or tourism. EO parameters can be associated to Maritime traffic 10,11 and aviation 12,13 as a proxy for touristic activity, trade and exchange. Fluctuations in the number of containers 14,15 located in a port or other depots can be associated with macro-economic trends.…”
Section: Motivationmentioning
confidence: 99%
“…GCC data is used, and the asymmetric ARDL method is applied to extract that all these blue economy factors add to the country's economic growth. Likewise, Fratila et al (2021) used maritime transport as a blue factor to check if it contributes to the economic growth of European Union countries. They used data for 11 years and found that investment in maritime transport is significantly and positively related to economic growth, and a 1% increase in these blue factors increases economic growth by 1.6%.…”
Section: Blue Factors and Sustainable Economic Growthmentioning
confidence: 99%